Ag@polyDOPA-b-polysarcosine hybrid nanoparticles with antimicrobial properties from in-situ reduction and NTA polymerization. (December 2019) - Cen, Jiayu; Zheng, Botuo; Yang, Yang; Wu, Jindan; Mao, Zhengwei; Ling, Jun; Han, Guocan
Graphical abstract: Highlights: Conditions are optimized for polymerization of NTAs to synthesize PDOPA-b-PSar. Ag@PDOPA-b-PSar nanoparticles are prepared after the reduction of Ag(I) by PDOPA-b-Psar. More than 95% bacterial killing efficiency to E.coil and S.aureus by Ag@PDOPA-b-PSar nanoparticles. Abstract: Poly(α-amino acid)s are promising materials due to their excellent biocompatibility and biodegradability. α-Amino acid N-thiocarboxyanhydrides (NTAs), the thio-analogues of the corresponding N-carboxyanhydrides (NCAs), are able to synthesize polypept(o)ides by ring-opening polymerization with the tolerance of hydroxyl's nucleophilic attack. In this work, polyDOPA-b-polysarcosine (PDOPA-b-PSar, named as DoS) copolymers are synthesized by sequential polymerizations of 3, 4-dihydroxy-L-phenylalanine N-thiocarboxyanhydride (DOPA-NTA) and sarcosine N-thiocarboxyanhydride (Sar-NTA) initiated by benzylamine in tetramethylene sulfone. With the reduction of catechol ligand, PDOPA-b-PSar act as the reducing and stabilizing agents for silver nanoparticles. The obtained Ag@PDOPA-b-PSar (Ag@DoS) nanoparticles have the average diameters of 81 nm with 10 nm core and narrow distributions. More than 95% bacterial killing efficiency to E.coil and S.aureus by Ag@DoS nanoparticles shows the potential for biomedical applications.